2022
DOI: 10.36227/techrxiv.19657320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conceptualization of Blockchain Enabled Interconnected Smart Microgrids

Abstract: <p> Power systems are undergoing rapid transitions to incorporate renewable sources of generation and to combat climate change. Next stage of transitions will lead to a shift from large-scale, centralized systems to networks of smallsized, distributed electricity systems which require distributed or decentralized ledgers for database management for efficient transactions. Distributed Ledger Technology (DLT) are a form of decentralized ledgers where the transactions (energy, information and money) among v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…While interoperability has been discussed and implemented to a certain extent in DeFi, the energy sector is yet to discuss and implement it. This topic has been mentioned in [5] and addressed in limitation in [14]. The current paper recognizes the before mentioned reasons for the need for interoperability between heterogeneous BSMGs (or individual users) and tries to provide a solution.…”
Section: Introductionmentioning
confidence: 93%
“…While interoperability has been discussed and implemented to a certain extent in DeFi, the energy sector is yet to discuss and implement it. This topic has been mentioned in [5] and addressed in limitation in [14]. The current paper recognizes the before mentioned reasons for the need for interoperability between heterogeneous BSMGs (or individual users) and tries to provide a solution.…”
Section: Introductionmentioning
confidence: 93%
“…These works involve transactions between homogeneous chains or chains implemented on the same BCT platform. Since complete and true interoperability involves transactions between heterogeneous chains too, this research problem has not been sufficiently explored and is currently a research gap which has been identified in [5], [14] and addressed in this paper. The challenges regarding scalability and interoperability are mentioned in [5] while a conceptual discussion is conducted in [14].…”
Section: B Related Work In Energy Sectormentioning
confidence: 99%
“…Since complete and true interoperability involves transactions between heterogeneous chains too, this research problem has not been sufficiently explored and is currently a research gap which has been identified in [5], [14] and addressed in this paper. The challenges regarding scalability and interoperability are mentioned in [5] while a conceptual discussion is conducted in [14]. The latter proposes executing interactions between Ethereum, Hyperledger and Tendermint platforms through IBC, but does not discuss the required setup or the practical implementation.…”
Section: B Related Work In Energy Sectormentioning
confidence: 99%
See 2 more Smart Citations